THE School of Botany in the Brussels Botanic Garden (1797-…): FROM CENTRE TO MARGINS (Museologia & Interdisciplinaridade, 2016)
This work sketches the history of the School of (Systematic) Botany that was planted in the Brussels Botanic Garden since its early establishment in 1797 to our days. It depicts the changes that were brought to this very peculiar area as well as the evolving attention it underwent under the gun of several factors. These factors not only included switches in scientific paradigms, but political changes also, changes in mentalities, among other things, that impacted the Belgian society. As a case study, the following pages tend to focus on local situations and sources. In addition it intends to encourage further studies not merely on the Schools of Botany and the different kinds of botanic gardens they were embedded in, but on the other types of Schools that surfaced with time and the roles they were given too.